Effectiveness of Physical and Psychological Treatment for Cancer-Related Fatigue: Systematic Review - Wulan Syafitry; Dian Hudiyawati (Jurnal Kesehatan, 2021)
Cancer is the second leading cause of death worldwide. Fatigue is one of the most common side effects of people with cancer. The range of people with cancer who experience fatigue is 70-80%, when undergoing cancer treatment and during the phase before and after treatment. This systematic review aims to identify fatigue management with non-pharmacological intervention. The journals selected from 2015 to 2020 in an international database: Pubmed, SAGE journals, Microsoft Academic, and Science Direct. The database searched using the keywords "exercise treatment" OR "psychological treatment," AND "fatigue" OR "cancer-related fatigue," AND "during cancer treatment" OR "after cancer treatment." Assessment of Critical quality appraisal uses tools from the JBI (Joanna Briggs Institute) critical assessment checklist. The method of analysis used the descriptive method. The results of the Systematic review found 13 journals that met the inclusion criteria, the total sample was 1365 respondents with an average age of 56.85, and the consequences of female respondents were 857 respondents, and male respondents were 464 respondents. Physical treatment and psychological treatment can reduce cancer fatigue before and after treatment. The interventions given both physical treatment and psychological treatment have their benefits and vary in their effectiveness.